ANALISIS KEBUTUHAN APLIKASI WMA (WORKLOAD MEASUREMENT ANALYSIS) BERBASIS ANDROID UNTUK PERHITUNGAN ANALISIS BEBAN KERJA DI RSI AMINAH BLITAR - Shofa Athur Rosyida; Dea Allan Karunia Sakti; Rahmadyo Yudhi Prabowo (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2023)
Aminah Islamic Hospital in Blitar City has workload problems, including calculations that are still done manually, long workload calculation formulas that also make it difficult for officers to carry out monitoring, rarely do evaluations resulting in uneven workloads, and. In this 4.0 era, it is possible to have an information system to assist in the process of calculating workload analysis. In making an information system analysis is needed according to user needs. Needs analysis is useful for determining what information systems should be done in a problem solving. This is done to identify strengths, weaknesses, and opportunities for improvement. The purpose of this study was to analyze the needs of the Android-based WMA (Workload Measurement Analysis) application for calculating workload analysis at RSI Aminah Blitar. This research method uses descriptive research with a qualitative approach. This study resulted in an analysis of the needs of the WMA application using an Android-based smartphone. The WMA application menu consists of a login display, data input, conclusion, and history so as to produce a WMA application that fits user needs to calculate workload requirements analysis at RSI Aminah Blitar.